“Language is the Сonfession of the Nation...” (Following the Meeting of Interdisciplinary Discussion Club) - M. K. Kabardov; O. A. Moskvitina (Научный диалог, 2017)
The results of the meeting of the interdisciplinary scientific discussion club at the Psychological Institute of the Russian Academy of Education (Moscow) are presented. It is reported that the meeting discussed the problem of the current state of language as a phenomenon of culture and intercultural communication. The main issues that were discussed in the framework of the scientific meeting are highlighted.